Forest Honey Diversity and Potential for Honey-Based Agrotourism in Sumbawa Regency - Yadi Hartono; Syafruddin Syafruddin; Wahyudi Hadiatma Taqwa (Journal of Biology, Environment, and Edu-Tourism, 2025)
Sumbawa Regency is known for its unique forest honeybee commodities and has the potential to be utilized in agro-tourism development. This study aims to determine the species of Sumbawa tropical forest honeybees and their potential to be integrated in agro-tourism development. Data collection methods used literature review, observation, and interviews. The results showed that Sumbawa tropical forest honey species include A. dorsata and Trigona spp. The diversity of flavors, colors, benefits, and the uniqueness of the collection process can be developed into agritourism.  The development of honey-based agro-tourism can be directed towards educational, ecological, and local economic aspects. Therefore, strengthening local institutions through the contribution of government, investors, and the community in realizing superior commodities of honey bee products in the agro-tourism sector.